Evaluation of the effectiveness of an eLearning program in the nursing observation and assessment of acute surgical patients: A naturalistic observational study. (August 2021) - Glanville, David; Kiddell, Jane; Lau, Rosalind; Hutchinson, Ana; Botti, Mari
Abstract: Aim/objective: The aim of this study was to evaluate the effectiveness of an eLearn program in changing surgical nurses' approach to clinical assessment. Background: Nurses need to have the knowledge and skills to recognise and respond to changes in patients' physiological condition in a timely manner. A private health service in Melbourne, Australia developed an online (eLearn) program highlighting the importance of clinical assessment and provided nurses with an overview of the Airway, Breathing, Circulation, Disability, Exposures ('ABCDE') approach. Design: A before and after study design that involved naturalistic observation of nurse-patient interactions and nurses' performing patient clinical assessments was undertaken on two surgical wards. Methods: The intervention ward nurses received standard education and exposure to the eLearning program. The comparison ward nurses received standard workplace education on patient assessment. The nurses were observed from May to August 2018. Results: Following completion of the eLearn, intervention ward nurses were observed to spend more time with their patients conducting clinical assessment. On both wards, not all nurses performed comprehensive ABCDE assessment and there was variability associated with the sequencing of ABCDE assessment. Conclusions: This study provides some evidence that completion of an eLearn can change clinical practice, however the intensity of the intervention was insufficient to achieve optimal practice in the conduct of clinical assessments. Highlights: Nurses were inconsistent when performing post-operative patient's assessment. Online training improved behaviour change in conducting clinical assessment. Online training was insufficient to achieve optimal clinical assessment practice.